The impact of digital economy on agricultural green total factor productivity: evidence from the quasi-natural experiment of the “Broadband China” Strategy - Wang, Luanfeng; Cai, Yuhui (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe empowerment of agricultural green transformation through the digital economy has emerged as a critical pathway toward sustainable development.MethodsUtilizing panel data from 286 Chinese cities spanning from 2011 to 2023, this study employs the “Broadband China” Strategy as a quasi-natural experiment to construct a multi-period difference-in-differences (DID) model. We examine the impact of the digital economy (DE) on agricultural green total factor productivity (AGTFP), while also exploring its underlying mechanisms, heterogeneous characteristics, and spatial spillover effects.ResultsThe findings reveal the following: (1) The DE significantly enhances AGTFP. (2) This enhancement is driven by green technology innovation, environmental regulation, and financial development. (3) The impact of DE on AGTFP varies across natural geographical factors and socio-economic factors. (4) Positive spatial spillover effects are observed in the impact of DE on AGTFP.DiscussionThis study highlights that to achieve sustainable agricultural growth, it is crucial to continuously promote rural digital economy development, leverage financial instruments to support agricultural green transformation, implement region-specific development strategies, and strengthen inter-regional cooperation and communication.